From the Past to the Present in Time Future. Disciplines in the Humanities and Social Sciences - Dulyakasem, Uthai (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
This very short article aims to point to the fact that in the present era where the progress of science and technology is in its high gear, it has destroyed the old value system and at the same time created many new value systems, such as consumerism, materialistic success and the value, which gives great importance to speed and more importantly, perhaps, it destroyed the diversity, which is the foundation of ecological as well as socio-cultural systems. The article therefore strongly recommends that the younger generation must seriously reconsider to study Humanities and Social Sciences in both their contents and methodologies so that human value will be restored and vitalized. Without these values, it will be impossible to expect that our world would be in peace and the people will live with true happiness despite the support of modern technology.